Participacija učenika putem primjene i procjene uspješnosti MAPS tehnike osobno usmjerenog planiranja : studija slučaja - Opačak, Tatjana (Array, 2019)
Within the frame of the concept of inclusive education in which the active participation of students with disabilities and individualized support of great importance to educational success and personal satisfaction of students, we applied and evaluated the MAPS technique of person-centered approach to planning for the student of the 5th-grade elementary school. The study was conducted as a case study for a student with disabilities with a total of 14 respondents of whom 10 adults and four fifth grade students. The data were collected through interviews with all participants and observation of the student for whom MAPS was applied. By qualitative data processing, we gained a clearer insight into the subjective experiences and emotions of the participants. Those are divided into 5 thematic areas. A positive contribution to person-centred planning on the quality of life of students with disabilities (greater acceptance of pupils in the classroom environment, development of student social and communication skills, friendship, leisure time) has been noted, which can contribute to the easier adaptation of student to the demands placed by higher classes elementary schools. The conducted research indicates the importance of using MAPS as a way of individualized support for students with disabilities. At the same time, it emphasized the necessity of participation of students with disabilities and their peers in the planning and the implementation of MAPS process. MAPS technique of person-centered planning is a good example of inclusive practice in the general educational system.